Evaluasi Kinerja dan Tingkat Pelayanan pada Simpang Gampong Beusa Kabupaten Aceh Timur - muhammad aziz; Iqbal; Putri Balqis (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
Regional development and increasing economic activities in East Aceh Regency have led to a rise in traffic volume, particularly at major intersections that connect sub-districts and regencies, such as the Gampong Beusa Intersection in Peureulak Barat District. This intersection is an unsignalized three-leg intersection that connects the Medan–Banda Aceh national road with access to Serbajadi District (Lokop). The increase in vehicle volume, especially heavy vehicles related to petroleum industry activities, has caused traffic delays and potential traffic conflicts at the intersection.This study aims to analyze the traffic performance of the Gampong Beusa Intersection and determine its Level of Service (LOS). The analysis method used refers to the Indonesian Highway Capacity Manual (MKJI) 1997 for unsignalized intersections. Primary data were obtained through traffic volume surveys and geometric measurements of the intersection conducted over three days, namely Monday, Thursday, and Saturday during the morning, midday, and evening peak hours. Secondary data in the form of population statistics were obtained from the Central Bureau of Statistics of East Aceh Regency.The analysis results show that the actual intersection capacity, after considering adjustment factors, ranges from 1,782 to 1,825 pcu/hour. The Degree of Saturation (DS) for each approach ranges from 0.57 to 0.69, with an average value of 0.64, indicating that the traffic condition is still below the saturation level. The average vehicle delay ranges from 24 to 27 seconds per vehicle. Based on the delay value, the intersection Level of Service is categorized as LOS D. This condition indicates that the intersection can still operate, but traffic flow has begun to become unstable during peak hours, thus requiring efforts to improve intersection performance in the future.